Kepedulian Mahasiswa dalam Mewujudkan Lingkungan Bebas Sampah melalui Partisipasi Sosial dan Perilaku Ramah Lingkungan - Budi Handayani; Pingki Aurel Laisyah; Rommy Hardyansah; Muhammad Yusron Maulana El-Yunusi; Eli Retnowati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The problem of waste in the student environment is still a major issue due to low awareness and inconsistent waste management behavior. Students have a strategic role in building a clean campus environment through active and collaborative participation. This Community Service (PkM) activity aims to increase student awareness and participation in environmental management with an Asset Based Community Development (ABCD) approach. The activity was held on Friday, October 3, 2025 at the East Java Provincial Environment Agency (DLH) and the area around the Afvoer Kemamang waterway, Surabaya. The stages of activities include discovery, dream, design, define, and delivery to design and implement structured and sustainable environmental programs. The results of the activities show an increase in student awareness and involvement in environmental cleanup actions, social media-based waste management education, and the formation of environmental care groups at the faculty level. Students began to implement environmentally friendly behavior consistently. These findings confirm that strengthening asset-based social participation is effective in forming a culture of environmental care in the campus environment.